Hubungan Antara Transparency dengan Partisipasi Donor Darah Sukarela Di Mobile Unit Upt Transfusi Darah Dinas Kesehatan Provinsi Sulawesi Selatan - Rahma, Siti; Yusriani, Yusriani; Makmun, Armanto (Innovative: Journal Of Social Science Research, 2025)
Abstract WHO standards state that every country should have a blood supply of at least 2% of its population. In Indonesia, ideally there should be around 5.5 million blood bags, but currently only around 4 million blood bags are available per year. This is due to a lack of public participation. Participation can be influenced by internal and external factors such as the transparency of blood donation officers. This study aims to determine the relationship between transparency and voluntary blood donor participation. Method: This study uses a quantitative research method with a cross-sectional study design. Sampling in this study used accidental sampling with a total sample of 154 respondents. Data collection was conducted using questionnaires and processed using SPSS 22. The analysis used was chi-square. Results: This study found that there is a relationship between transparency and voluntary blood donation participation (p=0.000). Conclusion: Transparency of blood donation officers can increase voluntary blood donation participation. Keywords: transparency, participation, voluntary blood donation